Susceptibility of Microorganisms Isolated from Necrotic Pulps to Calcium Hydroxide - Gaetti Jardim Júnior, Elerson; Landucci, Luís Fernando; Dezan Júnior, Eloi; Okamoto, Ana Claudia; Holland, Roberto (ARCHIVES OF HEALTH INVESTIGATION, 2013)
Calcium hydroxide has been used as pulp-capping agent and canal dressing due to its antimicrobial and anti-inflammatory properties besides its ability to induce formation of mineralized tissues. The aim of this study was to evaluate the susceptibility to calcium hydroxide of 146 bacterial strains isolated from endodontic infections. MIC was determined by using an agar dilution method, while contact bactericide activity was performed through in broth. All the isolates were sensitive to calcium hydroxide in concentrations that varied from 0.5mg/ml to 128 mg/ml, and the genera Enterococcus, Pseudomonas, Staphylococcus and Actinomyces were the most resistant. Gram-negative anaerobes proved to be the most sensitive isolates. All the isolates were inhibited after 60 minutes of contact with the alkali in concentration of 100mg/ml. Keywords: Calcium Hydroxide; Microbial Sensitivity Tests; Infection; Dental Pulp; Bacteria.